If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 + -11 = 5(x + -2) Combine like terms: 46 + -11 = 35 35 = 5(x + -2) Reorder the terms: 35 = 5(-2 + x) 35 = (-2 * 5 + x * 5) 35 = (-10 + 5x) Solving 35 = -10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 35 + -5x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 35 + -5x = -10 + 0 35 + -5x = -10 Add '-35' to each side of the equation. 35 + -35 + -5x = -10 + -35 Combine like terms: 35 + -35 = 0 0 + -5x = -10 + -35 -5x = -10 + -35 Combine like terms: -10 + -35 = -45 -5x = -45 Divide each side by '-5'. x = 9 Simplifying x = 9
| 3m+11=4m+5 | | 80=32x-x | | 3+2=4 | | X-31/2=51/4 | | 7p=8+6p | | 9.9/10=w/20 | | ab-5=m | | 6/11n+35 | | 3x+57=13x-3 | | 4x/10= | | x+8=12-3x | | d/9=-2 | | K/15=5 | | a+a+5+4a-18=180 | | 3f+9f=-84 | | 7/j=385/55 | | 3n-2=2 | | 3(m-1)=2(m-3) | | (x-4)(x+4)/2 | | 2x+y=w | | 8/s=64/72 | | 7+4g=7-8g | | 1000-65x= | | -7=p/5-1 | | -3(3y-10)+2(2y+10)= | | 4(3-x)=-3(6-2x) | | 2x^2+3x+1=28 | | 5=0.5m-3 | | 4x-9=y | | (X/6)+8=22 | | 9x-2x=3x+2 | | 6.25=w/5 |